THOROUGH BIOINFORMATICS EXAMINATION REVEALS NOC4L AS A PROGNOSTIC INDICATOR IN LUNG ADENOCARCINOMA - A-Zaalan , Ayoob Radhi (PT. Antis International Publisher, 2025)
Objective: This study systematically investigates the prognostic significance of nucleolar complex-associated protein 4 homolog (NOC4L) in lung adenocarcinoma (LUAD) and explores its associations with clinicopathological parameters, immune microenvironment components, and molecular pathways. Method: A bioinformatics-based approach was applied using publicly available databases including Kaplan–Meier Plotter, GEPIA2, UALCAN, and TIMER2.0. Survival analyses encompassed overall survival (OS), disease-free survival (DFS), first progression survival (FPS), and post-progression survival (PPS). Correlations with tumor stage, nodal metastasis, histological subtypes, tumor-infiltrating immune cells, and p53 pathway genes were evaluated. Results: High NOC4L expression was consistently associated with poor prognosis across all survival indicators and correlated with advanced tumor stage, nodal metastasis, and aggressive histological forms. Elevated NOC4L expression showed positive correlations with immunosuppressive cells such as myeloid-derived suppressor cells and cancer-associated fibroblasts, and negative correlations with cytotoxic CD8⁺ T cells. Novelty: This study identifies NOC4L as a potential prognostic biomarker in LUAD, linking its overexpression to immune suppression and tumor aggressiveness, thereby suggesting its role in cancer progression and its potential as a therapeutic target.